ASSEMBLED FLOOR SLAB-TYPE STEEL/WOOD COMBINATION JOINT AND ASSEMBLY METHOD THEREFOR - LIU, Yi; MOU, Ben; LI, Zunqiang; FENG, Peng (2022)
An assembled slab-type steel-wood composite joint and an assembly method thereof are disclosed. The joint adopts an assembled steel-wood composite structure, so that the probability of joint destruction is lowered, and the overall bearing capacity of a building is improved. The composite joint comprises a steel-wood composite column, square wood beams, connecting assemblies for connecting the steel-wood composite column and the square wood beams, and wood slabs connected with and supported by the steel-wood composite column, the square wood beams and the connecting assemblies. The steel-wood composite column comprises a hollow cross-shaped outer square wood column, and square blocks are integrally formed on the outer square wood column; and a steel sleeve is inlaid in the outer square wood column, an inner wood column is inlaid in the steel sleeve, column vertical steel bars penetrate through the inner wood column, horizontal steel bars penetrate through the square blocks and are fixedly connected to the steel sleeve, and threads are arranged at the ends of the horizontal steel bars.